SISTEM OTOMASI PADA MODUL PROCESSING DENGAN MENGGUNAKAN SEQUENTIAL FUNCTIONAL CHART - Moergen Tandinata; Didi Widya Utama; Gatot Soeharsono (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Automation is a technology that can be used to implement an instructional process or an automatic procedure. In this framework that has been using an instructional program that combined with a control system to process an instruction or commands. This processing module is a part of the automation which checking a process simulation of hollow and not hollow objects, then a PLC is use to control the process as designed be needed to control all of the working processing modules systems works. working system, a programming language that easily to be understood is needed such as functional block diagram (FBD) is use to program a plc system which functional block diagram (FBD) is a method that can describe a function between input and output variable, in FBD there is a Sequential Function Chart method (SFC ) which control the program sequential activity. So this research discusses the control of processing module which based on FBD programming language by using the SFC method.